Atypical central auditory speech-sound discrimination in children who stutter as indexed by the mismatch negativity - Jansson-Verkasalo E; Eggers K; Jarvenpaa A; Suominen K; Van den Bergh B; De Nil L; Kujala T (ELSEVIER SCIENCE INC, 2022)
Purpose: Recent theoretical conceptualizations suggest that disfluencies in stuttering mayarise from several factors, one of them being atypical auditory processing. The main purposeof the present study was to investigate whether speech sound encoding and central auditorydiscrimination, are affected in children who stutter (CWS).
Methods: Participants were 10 CWS, and 12 typically developing children with fluent speech(TDC). Event-related potentials (ERPs) for syllables and syllable changes [consonant, vowel,vowel-duration, frequency (F0), and intensity changes], critical in speech perception andlanguage development of CWS were compared to those of TDC.
Results: There were no significant group differences in the amplitudes or latencies of theP1 or N2 responses elicited by the standard stimuli. However, the Mismatch Negativity(MMN) amplitude was significantly smaller in CWS than in TDC. For TDC all deviants of the linguistic multifeature paradigm elicited significant MMN amplitudes, comparable with the results found earlier with the same paradigm in 6-year-old children. In contrast, only the duration change elicited a significant MMN in CWS.
Conclusions: The results showed that central auditory speech-sound processing was typical at the level of sound encoding in CWS. In contrast, central speech-sound discrimination, as indexed by the MMN for multiple sound features (both phonetic and prosodic), was atypical in the group of CWS. Findings were linked to existing conceptualizations on stuttering etiology.